GUARANTEEING THE RIGHT TO ADEQUATE SCHOOL MEALS FOR STUDENTS WITH SPECIFIC DIETARY NEEDS: CHALLENGES, UPDATES, AND RECOMMENDATIONS FOR MUNICIPALITIES - de Paula, Flávia Anastácio; Garcia, Jaciara Reis Nogueira (Seven Editora, 2026)
This study aims to describe the challenges related to access to the right to health for students with special dietary needs within municipalities and in the preparation of school menus. This is an article systematized through the experience of nutritionists regarding the challenges faced in guaranteeing the Human Right to Adequate Food (HRAF) for children and adolescents with allergies, food intolerances, and/or celiac disease. The results showed that, despite the exclusion of certain foods and the development of specific menus to meet the needs of students with specific dietary requirements, significant challenges remain. Our intention is to contribute to reflections on the issue of students’ citizenship rights and on the importance of control, monitoring, and enforceability mechanisms to ensure these rights. This experience may serve as a stimulus for the development of child protection mechanisms, as well as for the promotion, prevention, and precautionary protection of children’s health in educational institutions, in addition to ensuring universal access to education.